CONTENT OF VOLUME 20 ISSUE 1 APRIL 2024 (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
MULTIDISCIPLINARY PERIODONTIA-ORTHODONTIA APPROACH IN A CASE OF MIDLINE DIASTEMA WITH LABIAL FRENECTOMY USING ELECTROSURGERYMedia Sukmalia Adibah, Eka Pramudita Ramadhany, Valeo Adika Laksana, Ni Luh Desy Ayu Susilahati1 - 6 RE-TREATMENT OF MISMANAGED BILATERAL CONDYLAR FRACTURE AND POST-SURGICAL COMPLICATIONOyagi Shuka, Nyoman Ayu Anggayanti, Anak Agung Manik Swayoga, Agus Dwi Sastrawan, Eka Marwansyah Oli’i7 - 14 THE RELATIONSHIP OF ORAL HEALTH AND QUALITY OF LIFE FOR ELDERLY AT THE TRESNA WERDHA NIRWANA SOCIAL ORGANIZATION PURI SAMARINDAAlifia Auralia, Nuryanni Dihin Utami, Endang Sawitri, Elliana Martalina, Ronny Isnuwardana, Cicih Bhakti Purnamasari15 - 21 EFFECT OF BROWN ALGAE (Sargassum Sp) GEL ON ALKALINE PHOSPHATASE LEVELS IN PERIODONTITIS RATS INDUCED BY SILK LIGATION MODELMuhamat Muhtar S Abdurrohman, Faruq Abdurrohman Muhammad, Tahta Danifatis Sunnah, Ade Ismail A. K, Christina Mahardika22 - 28 THE RELATIONSHIP OF KNOWLEDGE AND THE BEHAVIOR OF DENTAL POST GRADUATED STUDENTS REGARDING PERSONAL PROTECTIVE EQUIPMENT AT RSGM SARASWATI DENPASARDwiastutik Listiantari, Ni Luh Gede Aris Maytadewi Negara, Agnes Ayu Biomi29 - 33 COMBINATION OF REGENERATIVE THERAPY AND FREE GINGIVAL GRAFT IN STAGE IV PERIODONTITIS: CASE REPORTResky Ramadhani, Ayu Rahayu Feblina, Dian Setiawati34 - 39 EFFECT OF KECEMCEM (Spondias pinnata) EXTRACT ON ANGIOGENESIS OF GINGIVA AFTER CURETASE OF WISTAR RATSEka Pramudita Ramadhany, Media Sukmalia Adibah, I Ketut Suandika Dharma Yanta40 - 45 EFFECT OF 4 wt% HYDROXYAPATITE PASTA ON DENTAL EMAIL HARDNESSJames Hartono Santoso, Anastasia Elsa Prahasti, Elline46 - 52 TEST OF RESISTANCE OF ALPUKAT (Persea americana mill) FRUIT EXTRACT ON THE GROWTH OF THE Streptococcus mutansPutu Rusmiany, Nyoman Nurdeviyanti, Ilma Yudistian, Agnesia Lorenza53 - 59 DIFFERENCES IN FLOW RATE AND SALIVA PH IN USERS AND NON-USERS OF FIXED ORTHODONTIC APPLIANCESViona Sekar Melati, Ernawati, Ageng Wicaksono60 - 66 THE EFFECTIVENESS OF PLATELET RICH FIBRIN, CONNECTIVE TISSUE GRAFT AND THEIR COMBINATION IN THE CLOSURE OF GINGIVAL RECESSION: A SYSTEMATIC REVIEWDian Anggraini, Irma Ervina, Aini Hariyani Nasution67 - 75 QUANTITATIVE ANALYSIS OF THE COMPLETENESS OF GENERAL POLY OUTPATIENT MEDICAL RECORD DOCUMENTS AT COMMUNITY HEALTH CENTER I EAST DENPASARAnak Agung Putri Adnyaswari, Putu Ika Farmani, Made Karma Maha Wirajaya76 - 82 POTENTIAL OF VIRGIN COCONUT OIL PASTE AS EXTRINSIC DENTAL STAIN REMOVALKhusnul Munika Listari, Siham83 - 89 THE EFFECTIVENESS OF METRONIDAZOLE GELS IN THE MANAGEMENT OF PERIODONTAL DISEASECitra Jasmin Cangara, Hasanuddin Thahir90 - 95 THE BENEFICIAL EFFECTS OF PROPOLIS ON OSTEOBLAST DIFFERENTIATION: A LITERATURE REVIEWJessy Wijaya, Rezmelia Sari, Suryono96 - 102 INCIDENCE OF ORAL CANDIDIASIS IN FIXED ORTHODONTIC APPLIANCESWahyuni Dyah Parmasari, Masfufatun, Tri Juliati103 - 107 LASER-ASSISTED CROWN LENGTHENING: CLINICAL EFFICACY AND ADVANTAGES OVER CONVENTIONAL TECHNIQUES (SYSTEMATIC REVIEW)Rieska Rachmasari, Fatimah Maria Tadjoedin108 - 117 REGENERATIVE PERIODONTAL TREATMENT AS MANAGEMENT OF CHRONIC PERIODONTITIS: A CASE REPORTAinun Isnaeni Ilham, Daniel Tetan El, Sri Oktawati118 - 123 CHITOSAN COLLAGEN HYDROGEL: A POTENTIAL SCAFFOLD BIOMATERIAL FOR PERIODONTAL REGENERATIVE TREATMENTDharmmesti Anindita Wijayanti, Dahlia Herawati, Vincensia Maria Karina, Kwartarini Murdiastuti124 - 132 EFFECTIVENESS OF SOCKET PRESERVATION IN MAINTAINING ALVEOLAR BONE VOLUME: A SYSTEMATIC REVIEWFahrur Rozi Lubis, Irma Ervina, Martina Amalia133 - 138 CONVOLUTIONAL NEURAL NETWORK (CNN) BASED ON ARTIFICIAL INTELLIGENCE IN PERIODONTAL DISEASES DIAGNOSISNurul Huda Danial, Dian Setiawati139 - 148 FUNCTIONAL CROWN LENGTHENING AS A PRE-RESTORATIVE PROCEDURE IN THE AESTHETIC ZONEVidya Nursolihati, Osa Amila Hafiyyah149 - 155 MANAGEMENT OF BACTERIAL PLAQUE-INDUCED GINGIVAL ENLARGEMENT: CASE REPORTMartina Amalia, Cut Ati Ningsih, Widianto Meydhiono156 - 163 EFFECT OF SOLVENT TYPE ON THE AMOUNT OF YIELD FROM MACERATION OF MORINGA PLANTS (Moringa oleifera)Wulan Anggestia, Sri Pandu Utami, Darmawangsa,Widya P. Sari, Difa Dirgantara164 - 169 FIXED DOSE COMBINATION OF MECOBALAMIN AND PREGABALIN IN THE TREATMENT OF OROFACIAL NEUROPATHIC PAINManuel Dwiyanto Hardjo Lugito170 - 175